Diet and kidney disease in high-risk individuals with type 2 diabetes mellitus - Dunkler, Daniela; Dehghan, Mahshid; Teo, Koon K.; Heinze, Georg; Gao, Peggy; Kohl, Maria; Clase, Catherine M.; Mann, Johannes; Yusuf, Salim; Oberbauer, Rainer (JAMA Internal Medicine, 2013)
Type 2 diabetes mellitus and associated chronic kidney disease (CKD) have become major public health problems. Little is known about the influence of diet on the incidence or progression of CKD among individuals with type 2 diabetes.To examine the association between (healthy) diet, alcohol, protein, and sodium intake, and incidence or progression of CKD among individuals with type 2 diabetes.All 6213 individuals with type 2 diabetes without macroalbuminuria from the Ongoing Telmisartan Alone and in Combination With Ramipril Global Endpoint Trial (ONTARGET) were included in this observational study. Recruitment spanned from January 2002 to July 2003, with prospective follow-up through January 2008.Chronic kidney disease was defined as new microalbuminuria or macroalbuminuria or glomerular filtration rate decline of more than 5% per year at 5.5 years of follow-up. We assessed diet using the modified Alternate Healthy Eating Index (mAHEI). The analyses were adjusted for known risk factors, and competing risk of death was considered.After 5.5 years of follow-up, 31.7% of participants had developed CKD and 8.3% had died. Compared with participants in the least healthy tertile of mAHEI score, participants in the healthiest tertile had a lower risk of CKD (adjusted odds ratio [OR], 0.74; 95% CI, 0.64-0.84) and lower risk of mortality (OR, 0.61; 95% CI, 0.48-0.78). Participants consuming more than 3 servings of fruits per week had a lower risk of CKD compared with participants consuming these food items less frequently. Participants in the lowest tertile of total and animal protein intake had an increased risk of CKD compared with participants in the highest tertile (total protein OR, 1.16; 95% CI, 1.05-1.30). Sodium intake was not associated with CKD. Moderate alcohol intake reduced the risk of CKD (OR, 0.75; 95% CI, 0.65-0.87) and mortality (OR, 0.69; 95% CI, 0.53-0.89).A healthy diet and moderate intake of alcohol may decrease the incidence or progression of CKD among individuals with type 2 diabetes. Sodium intake, within a wide range, and normal protein intake are not associated with CKD.clinicaltrials.gov Identifier: NCT00153101.
EVALuna2:4020